Analisis Pangsa Pengeluaran Pangan Rumah Tangga Miskin Petani Kelapa Sawit Di Kecamatan Sinunukan Kabupaten Mandailing Natal - Amnilis; Gusriati; Septia Mariani (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to determine the share of food expenditure of poor households and to analyze the effect of income, education of the head of the family, number of household members, length of household, amount of subsidized Raskin, non-food expenditure on the share of food expenditure of poor households in Sinunukan District, Mandailing Natal Regency. This research was conducted from September 10 to October 10, 2021. The location of the research was determined purposively with a total sample of 79 people. The data used are primary and secondary data. The method used in this research is descriptive analysis method using multiple linear regression analysis. Research results: 1. The share of food expenditure for poor households in Sinunukan District is 63% (food insecure households), : 2. The variables that partially have a significant effect on the share of food expenditure of poor households of oil palm farmers, Sinunukan Subdistrict, Mandailing Natal Regency, are income and non-food expenditure variables. Meanwhile, together (simultaneously) are household income variables, head of household education, number of family members, length of household, number of poor people received and non-food expenditure with sig 0.000 < 0.05, the value of the coefficient of determination is 0.883.